Heidegger, an approach to the relationship: thinking, being, language and education (Papeles, 2021)
The Martin Heidegger philosophy seeks to unmask prejudices that have been established since ancient times around what has been called and is still called thinking; it leads to the need to overcome habitual ways of modern thought under which we interpret the world and consider ourselves as rational thinking beings. To unravel this question this text proposes an interpretation of the thinking from what could mean a metaphysical study; it is so because for Heidegger metaphysics performed meditation always of the essence of being and truth.
Keywords: Heidegger; metaphysics; be; time; think